Wound and Skin Healing in Space: The 3D Bioprinting Perspective - Cubo-Mateo, Nieves; Gelinsky, Michael (Frontiers in Bioengineering and Biotechnology, 2021)
Skin wound healing is known to be impaired in space. As skin is the tissue mostly at risk to become injured during manned space missions there is the need for a better understanding of the biological mechanisms behind the reduced wound healing capacity in space. In addition, for far-distant and long-term manned space missions like the exploration of Mars or other extraterrestrial human settlements, e.g. on the Moon, new effective treatment options for severe skin injuries have to be developed. However, they need to be compatible with the limitations concerning the availability of devices and materials present in space missions. 3D bioprinting (BP) might be or become a solution for both demands as it allows the manufacturing of multicellular, complex and three-dimensional tissue constructs, which can serve as models in basic research as well as transplantable skin grafts. The perspective article provides an overview of the state-of-the-art of skin BP and approaches to establish this additive manufacturing technology in space. In addition, the several advantages of BP for utilization in future manned space missions are highlighted.